PEMBUATAN KOMPOSIT SERAT SERABUT KELAPA DAN RESIN FENOL FORMADEHIDE SEBAGAI MATERIAL PEREDAM AKUSTIK - Kartikaratri, Yohana Maya; Subagio, Agus; Widyandari, Hendri (BERKALA FISIKA, 2012)
The sound pollution due to noise is a one clasical problem in Indonesia. Theloudness can be reduced using the accoustic absorber. The composites of coconut fiberhas potential application as an environmental friendly accoustic absorber which is usingan agriculture waste. We reported the preparation of composite of coconut fiber as amatrix material and fenol formaldehide served as binder (coconut fiber/FF composite).The immersion of coconut fibers in the NaOH solution of 2% for 4 hours were caried outpriorly for improving the strengthness.The absorption coefficient (α) of the preparedcoconut fiber/FF composite was observed using two microphone impedance tube method(ISO 10534 – 2 dan ASTM E1050 – 08. The value of tested absorption coefficient (α) allof composites samples have fulfilled the requirement. Requirement of acoustic absorbervalue of α is more than 0,15; and all of composites samples fulfilled the requirement onfrequency 752 Hz - 6400Hz. Keyword : absorption coefficient, acoustic absorber, composite, coconut fiber, fenolformaldehid.